Studies toward the total synthesis of cytospolide E - Vadhadiya, Paresh M.; Rout, Jeetendra K.; Ramana, C. V. (Tetrahedron, 2015)
In this manuscript, we describe various approaches that we have examined towards the total synthesis of Cytospolide E. We initially attempted the RCM approach employing first and second generation Grubbs and Grubbs-Hoyeda catalysts resulting in the exclusive synthesis of the Z-isomer of Cytospolide E. With the Furstner catalyst, the dimerization involving the less hindered olefin was the exclusive event. Alternative approach documented is a successful cross-metathesis leading to a seco-acid with the requisite E-configuration and undesired macrodiolide formation during the attempted Shiina's lactonization. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 20-Membered macrodiolide; Nonenolide; Ring closing metathesis; Shiina lactonization; Yamaguchi esterification